Significant correlation of angiotensin converting enzyme and glycoprotein IIIa genes polymorphisms with unexplained recurrent pregnancy loss in north of Iran - Shokoufeh Fazelnia; Touraj Farazmandfar; Seyed Mohammad Bagher Hashemi-Soteh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Spontaneous abortion is considered as the most complex problem during pregnancy. Thrombophilia is resumed as a cause of recurrent pregnancy loss (RPL). Glycoprotein IIIa (GPIIIa) gene is involved in thrombosis and abortion. Angiotensin converting enzyme (ACE) converts angiotensin I to angiotensin II and is involved in thrombosis. The most common polymorphism in this gene is the insertion/deletion (I/D). Objective: In this study, we analyzed the association between ACE I/D and GPIIIa c.98C >T polymorphisms in women with unexplained RPL from the north of Iran. Materials and Methods: Sample population consisted of 100 women with unexplained RPL and 100 controls. The ACE I/D and GPIIIa c.98C>T polymorphisms were genotyped by TETRA-ARMS PCR. The association between genotypes frequency and RPL were analyzed using χP2P and exact fisher tests. Associated risk with double genotype combinations was also investigated by binary logistic regression. Results: There was significant association between ACE DD genotype and RPL (OR=2.04; 95% CI=0.94-4.44; p=0.036). ACE D Allele was also significantly associated with the RPL (OR=1.59; 95% CI=1.05-2.41; p=0.013). No significant association was observed between GPIIIa c.98C>T polymorphism and RPL. Conclusion: ACE I/D polymorphism may probably be a prognostic factor in female family members of women with the history of recurrent abortion